1983
DOI: 10.1016/s0022-5347(17)52645-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Epididymis in Testicular Descent

Abstract: In 54 patients with 70 undescended testes hospitalized for orchiopexy epididymal anatomy was examined intraoperatively. Of the testes 66 per cent had abnormal epididymides, which suggests a possibly significant role for the epididymis in the process of testicular descent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
3

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 10 publications
2
16
0
3
Order By: Relevance
“…Union by canalization of the rete testis and mesonephric tubules begins at 12 weeks and probably is completed at puberty (10). It has been speculated that an epididymal abnormality may interfere with the normal de- scent of the tesis (2,11,12), since the epididymis is normally attached to the gubernaculum, which guides the testis into the scrotum (13). During the process of normal testicular descent, the role of numerous mechanical components has been hypothesized, including a normal gubernaculum, epididymis, intra-abdominal pressure (13), and the innervation of the gubernaculum by the genitofemoral nerve (14).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Union by canalization of the rete testis and mesonephric tubules begins at 12 weeks and probably is completed at puberty (10). It has been speculated that an epididymal abnormality may interfere with the normal de- scent of the tesis (2,11,12), since the epididymis is normally attached to the gubernaculum, which guides the testis into the scrotum (13). During the process of normal testicular descent, the role of numerous mechanical components has been hypothesized, including a normal gubernaculum, epididymis, intra-abdominal pressure (13), and the innervation of the gubernaculum by the genitofemoral nerve (14).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of the epididymal anomalies is higher in association with ipsilateral patency of the processus vaginalis (71 to 78%) than with ipsilateral closure (16 to 38%) (2,3,6). Mininberg and Schlossberg found that if there was a patent processus Vaginalis, 78% of boys with undescended testis had epididymal anomalies, whereas only 38% had an abnormal epididymis if there was no associated hernia (2). Elder also showed that 64% of epididymides were abnormal when the processus vaginalis was completely patent, while only 11% were abnormal when the processus vaginalis was incompletely patent in boys with hydrocele/hernia or undescended testis (6).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations